(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2021)
The research to determine the potential for developing duck farming in Ternate City, especially Ternate Island and South Ternate Districts with the consideration that these areas have the highest population of duck breeders, and have potential development areas. The data collection method was carried out by observation, the sources of data obtained were primary and secondary data using qualitative and quantitative methods. The analysis used in this study is descriptive to describe the potential of the region, the potential of breeder resources, and the potential of individual breeders, while to see the economic potential using R/C-Ratio analysis. The results of the study indicate that the sub-districts of Ternate Island and South Ternate have potential areas for the development of ducks because they have a lower population density, so the area tends to be wider. The potential of breeder resources for the average breeder age is productive category, experienced in raising livestock. Economic potential by using R/C-Ratio analysis, the results of the feasibility test by obtaining an R/C-Ratio value of 2.7 (financially feasible), this indicates that if the addition of Rp.1 will get an income of 2.7. then the duck farming business in Ternate City has the potential and is feasible to be developed.